The Third Year-Students' Ability in Answering Synonymous Word Questions in Reading Comprehension of TOEFL-Like Tests at the English Department of Bung Hatta University - Lisa Tavriyanti; Laila Sakinah (English Language Education and Current Trends (ELECT), 2023)
The purpose of this research was to describe the third-year students’ ability in answering synonymous word questions in reading comprehension of the TOEFL Like test at the English Department of Bung Hatta University. The design of this research was descriptive research. The population of this research was third-year students at the English Department of Bung Hatta University. A total sampling technique was used, and the number of samples was 35 students. The instrument for collecting the data was reading comprehension of the TOEFL test. Based on the result analysis, the result of this research showed that the third-year students had low ability in answering synonymous word questions in reading comprehension of the TOEFL Like in the form of nouns, verbs, and adjectives. So, it can be concluded that the students’ ability in answering synonymous word questions in reading comprehension of the TOEFL Like was low.   REFERENCES Arikunto, S. (2015). Dasar-dasar evaluasi pendidikan (2nd ed.). Jakarta: PT Bumi Aksara. Birsch, J. R. (2011). Multisensory Teaching of Basic Language Skills, Third Edition. Baltimore, MD: Paul H. Brookes Publishing Company. Destiyanti, C., Amin, M., & Putera, L. J. (2021). Gender- based analysis of students ’ ability in answering factual and vocabulary-in-context questions of the toefl-like reading comprehension test. 9, 1–17. Elfiondri, Kasim, U., Mustafa, F., & Putra, T. M. (2020). Reading comprehension in the TOEFL PBT: Which sub-skill deserves more intensive training? TESOL International Journal, 15(1), 54–64. ETS. (2000). TOEFL program and service department computer-based TOEFL score user guide. New Jersey: Educational Testing Service. Fitria, T. N. (2021). Students ’ Ability in the Structure and Written Expression Section in Toefl. 8(2), 152–163. https://doi.org/10.22219/celtic.v8i2.16373 Gilakjani, A. P., & Sabouri, N. B. (2016). A Study of Factors Affecting EFL Learners ’ Reading Comprehension Skill and the Strategies for Improvement. 6(5), 180–187. https://doi.org/10.5539/ijel.v6n5p180 Hot Courses. (2016, October 17). Persyaratan Nilai Bahasa Inggris Untuk Kuliah S2 di Luar Negeri? https://www.hotcourses.co.id/study-abroad-info/university applications/persyaratan nilai-bahasa-inggris-untuk-kuliah-s2-di-luar-negeri Kampung Inggris. (2021, September 1). Standar Nilai TOEFL Untuk Melamar Kerja. https://kampunginggrisla.com/standar-nilai-toefl-untuk-melamar-kerja Matthiesen, S. J. (2017). Essential words for the TOEFL test of English as a foreign language (7th ed.) New York: BARRON'S. Merriam-Webster. (n.d.). Synonymous. In Merriam-Webster.com dictionary. Retrieved January 11, 2022, from https://www.merriam-webster.com/dictionary/writing Merriam-Webster. (n.d.). Question. In Merriam-Webster.com dictionary. Retrieved January 11, 2022, from https://www.merriam-webster.com/dictionary/writing Oyetunji, C. O. (2011). The effects of reading strategy instruction on L2 teacher trainees’ performance. University of South Africa. (Unpublished Master's Thesis) Retrieved from https://core.ac.uk/download/pdf/43170904.pdf Pressley, M. (2000). Comprehension Instruction: What Makes Sense Now, What Might Make Sense Soon? In M. L. Kamil, P. Mosenthal, P. D. Pearson, & R. Barr (Eds.), Handbook of Reading Research: Volume III. New York: Longman. Retrieved from http://www.readingonline.org/articles/handbook/pressley/index.html Putri, T. M. (2020). Reading Comprehension in the TOEFL PBT?: Which Sub-Skill deserves more Intensive Training?? 15(1). Samad, I. A., Jannah, M., & Fitriani, S. S., (2017). EFL students’ strategies dealing with common difficulties in TOEFL reading comprehension section. International Journal of Language Education, 1 (1). 29—36. Setyowaty, M et al., “Students’ Vocabulary Mastery on TOEFL Test: Does It Correlate with Reading Comprehension” International Conference on English Language Teaching, vol 434. Retrieved June 13, 2021 (3.58 pm) from https://www.researchgate.net/publication/341291580_Student's_Vocabulary_ Mastery_on_TOEFL_Test_Does_It_Correlate_with_Reading_Comprehension Wahyuni, Z., Ratmanida, & Marlina, L., (2018). The Relationship Of Students’ Metacognitive Reading Strategies Awareness And Reading Comprehension: The Case Of The Sixth Semester Student Of English Department Universitas Negeri Padang (UNP). Journal of English Language Teaching Volume 7 No. 3 Wardani, S. I. (2015). Improving Students ’ Vocabulary Mastery. Okara, 1, 132. Woolley, G. (2011). Reading comprehension: Assisting children with learning difficulties. New York: Springer. Yao, D. (2020). A comparative study of test takers’ performance on computer-based test and paper-based test across different CEFR levels. Canadian Centre of Science and Education. 13(1), 124-133.